Thallium scans in syndrome X. Issue 7 (July 1992) - Tweddel, Ann C; Martin, W; Hutton, I
Abstract : Objective —To review thallium scans in patients with angina and normal coronary arteriograms. Design —Retrospective review of data. Setting —Regional cardiac centre in Glasgow. Patients —100 patients selected from those undergoing diagnostic angiography for typical angina who had normal arteriograms (around 10%), no other cardiovascular abnormality, and available thallium scans (performed routinely before angiography). Main outcome measures —Coronary arteriography, exercise tests, and gated thallium scans at peak exercise. Results —The exercise test was positive in 30 and negative in 70 patients. Thallium defects were found in 98 patients, but no consistent pattern and no significant correlation existed between the extent of thallium defect and positive exercise test or exercise tolerance. Conclusions —Thallium defects described in 98 of 100 patients with angina and normal coronary arteriograms suggest that microvascular angina may be commoner than is generally appreciated.